THE USE OF DISTANCE LEARNING TECHNOLOGIES IN MEDICAL EDUCATION - Кравчук, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Browse dedicated distance learning technologies. Data on the history and development of distance education, interpretation of its content and features, advantages and disadvantages of using. Displaying current view on the introduction of distance learning in medicine and medical education system.